Interconnections between the Polarization Current and the Electromagnetic Signal of Rock Samples under Loading; Advanced Materials Research; Vol. 1085 : Prospects of Fundamental Sciences Development (PFSD-2014) - Yavorovich L. V. Ludmila Vasilievna; Bespalko (Bespal'ko) A. A. Anatoly Alekseevich; Fedotov P. I. Pavel Ivanovich; Popelyaev A. I. (Mathematical Methods in Materials Science, 2015)
Title screen